PERAN KOLABORASI DARING DALAM MENINGKATKAN KETERAMPILAN SOSIAL DAN KETERLIBATAN SISWA DI SEKOLAH DASAR: STUDI BIBLIOMETRIK - Nurlaila Nurlaila; Abas Oya; Nurlailatun Ramdani; Nurwalidainismawati Nurwalidainismawati (STKIP HARAPAN BIMA, 2024)
This study aims to analyze the role of online collaboration in enhancing social skills and student engagement in elementary schools from 2019 to 2024. Using a bibliometric approach, data were collected from Crossref through the Publish or Perish application, focusing on keywords such as